Information Kiosk Application Development at Taman Mini Indonesia Indah Jakarta - Qurrotul Aini; Eko Syamsuddin H.; Ahmad Zaky (UIN Sultan Syarif Kasim Riau, 2011)
Abstract Taman Mini Indonesia Indah (TMII) is a tourism site in Jakarta, which has area of 160 hectares and there are 26 traditional houses, 13 museums, 10 tourist parks, public and special facilities which are located far apart. Visitors needed information services that could help find the location, information and the facilities. Researchers proposed information kiosk applications as an alternative solution tool to help find the necessary information. The application development used multimedia development refers to Luther’s method; consist of concept, design, gathering materials, manufacture, testing, and distribution. The application interface includes nine designs, with dimension 950 x 700 pixels, 30 fps, capacity size of 291 MB, 18 pages, and duration of application 7 minutes 38 seconds. Based on questionnaire of 20 visitors, it could be concluded that the application was interested (80%), easy to use (80%), the information provided was clear (80%), and could assisted visitors to find the locations (90%). Keywords: information kiosks, database, multimedia, Taman Mini Indonesia Indah, Luther.